Enterprising communities grassroots sustainability innovations - Davies, Anna (Emerald, 2012)
This book provides an internationally grounded and critical review of grassroots sustainability enterprises, specifically focusing on the processes that lead to their formation, the governing context that shapes their evolution, the benefits they create and the challenges that they face in different contexts. This is the first internationally focused study of grassroots sustainability enterprises that covers such a range of environmental sectors. For the first time grassroots sustainability enterprises and their actions and impact receive comprehensive academic analysis from the perspective of their contribution towards more resilient development. The book begins by defining the term and placing it in context, looking at contemporary agendas in sustainability innovation and enterprise, and sustainability impacts and grassroots enterprises. It then examines a variety of grassroots sustainability enterprises such as low impact housing in the UK, eco-villages in Ireland, community gardening in Germany and turtle conservation in Costa Rica. It concludes by looking ahead to the future at governing frameworks for grassroots sustainability enterprises and smart green clean-tech economy.
Keywords: Nature -- General.; Nature -- Environmental Conservation & Protection.; Business & Economics -- Environmental Economics.; The environment.; Environmentalist thought & ideology.; Sustainability.; Sustainable living.; elektronické knihy; electronic books